ADAPTIVE PITCH-SHIFTING WITH APPLICATIONS TO INTONATION ADJUSTMENT IN A CAPPELLA RECORDINGS - Rosenzweig, Sebastian; Schwär, Simon; Driedger, Jonathan; Müller, Meinard (2021 24TH INTERNATIONAL CONFERENCE ON DIGITAL AUDIO EFFECTS (DAFX), 2021)
CRIS-Team WoS Importer:2022-08-19

A Dataset of Larynx Microphone Recordings for Singing Voice Reconstruction - Schwär, Simon; Krause, Michael; Fast, Michael; Rosenzweig, Sebastian; Scherbaum, Frank; Müller, Meinard (Transactions of the International Society for Music Information Retrieval, 2024)
ading: A Dataset of Larynx Microphone Recordings for Singing Voice Reconstruction Download A- Decrease article font size A+ Increase article font size Cite this article Print this article Alt. DisplayAlternative display Share: Share on Facebook Share on X Share on LinkedIn Share as email Dataset articles A Dataset of Larynx Microphone Recordings for Singing Voice Reconstruction Authors: Simon SchwärEmail Simon Schwär Michael Krause Michael Fast Sebastian Rosenzweig Frank Scherbaum Meinard Müller Toggle author information panel Abstract Larynx microphones (LMs) make it possible to obtain practically crosstalk-free recordings of the human voice by picking up vibrations directly from the throat. This can be useful in a multitude of music information retrieval scenarios related to singing, e.g., the analysis of individual voices recorded in environments with lots of interfering noise. However, LMs have a limited frequency range and barely capture the effects of the vocal tract, which makes the recorded signal unsuitable for downstream tasks that require high-quality recordings. In this paper, we introduce the task of reconstructing a natural sounding, high-quality singing voice recording from an LM signal. With an explicit focus on the singing voice, the problem lies at the intersection of speech enhancement and singing voice synthesis with the additional requirement of faithful reproduction of expressive parameters like intonation. In this context, we make three main contributions. First, we publish a dataset with over 4 hours of popular music we recorded with four amateur singers accompanied by a guitar, where both LM and clean close-up microphone signals are available. Second, we propose a data-driven baseline approach for singing voice reconstruction from LM signals using differentiable signal processing, inspired by a source-filter model that emulates the missing vocal tract effects. Third, we evaluate the baseline with a listening test and further show that it can improve the accuracy of lyrics transcription as an exemplary downstream tas
Keywords: Larynx Microphone; Singing Voice Reconstruction; Dataset; Differentiable Signal Processing; Singing Analysis

A Differentiable Cost Measure for Intonation Processing in Polyphonic Music - Schwär, Simon; Rosenzweig, Sebastian; Müller, Meinard (Proceedings of the International Society for Music Information Retrieval Conference (ISMIR), 2021)

Analysis of the Tbilisi State Conservatory Recordings of Artem Erkomaishvili in 1966 - Scherbaum, Frank; Müller, Meinard; Rosenzweig, Sebastian (Proceedings of the International Workshop on Folk Music Analysis, 2017)

A Web-Based Interface for Score Following and Track Switching in Choral Music - Zalkow, Frank; Rosenzweig, Sebastian; Graulich, Johannes; Dietz, Lukas; Lemnaouar, El Mehdi; Müller, Meinard (Late-Breaking and Demo Session of the International Conference on Music Information Retrieval (ISMIR), 2018)

Computer-assisted Analysis of Field Recordings: A Case Study of Georgian Funeral Songs - Rosenzweig, Sebastian; Scherbaum, Frank; Müller, Meinard (Journal of Computing and Cultural Heritage, 2022)

Dagstuhl ChoirSet: A Multitrack Dataset for MIR Research on Choral Singing - Rosenzweig, Sebastian; Cuesta, Helena; Weiß, Christof; Scherbaum, Frank; Gómez, Emilia; Müller, Meinard (Transactions of the International Society for Music Information Retrieval, 2020)
Choral singing is a central part of musical cultures across the world, yet many facets of this widespread form of polyphonic singing are still to be explored. Music information retrieval (MIR) research on choral singing benefits from multitrack recordings of the individual singing voices. However, there exist only few publicly available multitrack datasets on polyphonic singing. In this paper, we present Dagstuhl ChoirSet (DCS), a multitrack dataset of a cappella choral music designed to support MIR research on choral singing. The dataset includes recordings of an amateur vocal ensemble performing two choir pieces in full choir and quartet settings. The audio data was recorded during an MIR seminar at Schloss Dagstuhl using different close-up microphones to capture the individual singers’ voices. In this article, we give detailed insights into all stages of creating DCS: recording process, data preparation, generation of annotations as well as development of suitable interfaces for publicly accessing and reusing the data. Furthermore, we demonstrate the potential of the dataset for MIR research by discussing case studies on choral intonation assessment and multiple fundamental frequency (F0) estimation.<br
Keywords: Dagstuhl Choir; Set; Choral Music; Multitrack Recording; Choral Singing Analysis; F0

Detecting Stable Segments in F0 Trajectories for Harmonic Analysis of Traditional Georgian Vocal Music - Rosenzweig, Sebastian; Scherbaum, Frank; Müller, Meinard (Proceedings of the International Conference on Music Information Retrieval (ISMIR), 2019)

Erkomaishvili Dataset: A Curated Corpus of Traditional Georgian Vocal Music for Computational Musicology - Rosenzweig, Sebastian; Scherbaum, Frank; Shugliashvili, David; Arifi-Müller, Vlora; Müller, Meinard (Transactions of the International Society for Music Information Retrieval, 2020)
The analysis of recorded audio material using computational methods has received increased attention in ethnomusicological research. We present a curated dataset of traditional Georgian vocal music for computational musicology. The corpus is based on historic tape recordings of three-voice Georgian songs performed by the the former master chanter Artem Erkomaishvili. In this article, we give a detailed overview of the audio material, transcriptions, and annotations contained in the dataset. Beyond its importance for ethnomusicological research, this carefully organized and annotated corpus constitutes a challenging scenario for music information retrieval tasks such as fundamental frequency estimation, onset detection, and score-to-audio alignment. The corpus is publicly available and accessible through score-following web-players.<br
Keywords: Georgian Vocal Music; Artem Erkomaishvili; Score-Audio Annotations

Interactive Fundamental Frequency Estimation with Applications to Ethnomusicological Research - Müller, Meinard; Rosenzweig, Sebastian; Driedger, Jonathan; Scherbaum, Frank (Proceedings of the AES Conference on Semantic Audio, 2017)

libf0: A Python Library for Fundamental Frequency Estimation - Rosenzweig, Sebastian; Schwär, Simon; Müller, Meinard (Demos and Late Breaking News of the International Society for Music Information Retrieval Conference (ISMIR), 2022)

Multi-Media Recordings of Traditional Georgian Vocal Music for Computational Analysis - Scherbaum, Frank; Mzhavanadze, Nana; Rosenzweig, Sebastian; Müller, Meinard (Proceedings of the International Workshop on Folk Music Analysis, 2019)

PCP Notebooks: A Preparation Course for Python with a Focus on Signal Processing - Müller, Meinard; Rosenzweig, Sebastian (Journal of Open Source Education, 2022)
Keywords: Jupyter; Preparation Course

Real-Time MIR Algorithms for Music-Reactive Game World Generation - Meier, Peter; Schwär, Simon; Rosenzweig, Sebastian; Müller, Meinard (Proceedings for the Workshop für Innovative Computerbasierte Musikinterfaces (ICMI), 2022)

Rechnergestützte Musikethnologie am Beispiel historischer Aufnahmen mehrstimmiger georgischer Vokalmusik - Scherbaum, Frank; Müller, Meinard; Rosenzweig, Sebastian (Proceedings of the GI Jahrestagung, 2017)

RELIABILITY ASSESSMENT OF SINGING VOICE F0-ESTIMATES USING MULTIPLE ALGORITHMS - Rosenzweig, Sebastian; Scherbaum, Frank; Müller, Meinard (2021 IEEE INTERNATIONAL CONFERENCE ON ACOUSTICS, SPEECH AND SIGNAL PROCESSING (ICASSP 2021), 2021)
CRIS-Team WoS Importer:2021-11-26

Scales Beyond Major and Minor - Scherbaum, Frank; Müller, Meinard; Mzhavanadze, Nana; Rosenzweig, Sebastian (2023)

Throat Microphones for Vocal Music Analysis - Scherbaum, Frank; Rosenzweig, Sebastian; Müller, Meinard; Vollmer, Daniel; Mzhavanadze, Nana (Late-Breaking and Demo Session of the International Conference on Music Information Retrieval (ISMIR), 2018)

Tonal Organization of the Erkomaishvili Dataset: Pitches, Scales, Melodies and Harmonies - Scherbaum, Frank; Mzhavanadze, Nana; Arom, Simha; Rosenzweig, Sebastian; Müller, Meinard (Universitätsverlag Potsdam, 2020)

Tonleitern jenseits von Dur und Moll - Scherbaum, Frank; Müller, Meinard; Mzhavanadze, Nana; Rosenzweig, Sebastian (2023)

Towards Computational Feedback for Western Choral Singing Assessment - Weiß, Christof; Schlecht, Sebastian; Rosenzweig, Sebastian; Müller, Meinard (Proceedings of the International Conference on Music Information Retrieval (ISMIR), 2019)

Towards measuring intonation quality of choir recordings: A case study on bruckner's locus iste - Weiß, Christof; Schlecht, Sebastian; Rosenzweig, Sebastian; Müller, Meinard (Proceedings of the 20th International Society for Music Information Retrieval Conference, ISMIR 2019, 2019)
Unaccompanied vocal music is a central part of Western art music, yet it requires excellent skills for singers to achieve proper intonation. In this paper, we analyze intonation deficiencies by introducing an intonation cost measure that can be computed from choir recordings and may help to assess the singers' intonation quality. With our approach, we measure the deviation between the recording's local salient frequency content and an adaptive reference grid based on the equal-tempered scale. The adaptivity introduces invariance of the local intonation measure to global intonation drifts. In our experiments, we compute this measure for several recordings of Anton Bruckner's choir piece Locus Iste. We demonstrate the robustness of the proposed measure by comparing scenarios of different complexity regarding the availability of aligned scores and multi-track recordings, as well as the number of singers per part. Even without using score information, our cost measure shows interesting trends, thus indicating the potential of our method for real-world applications.
CRIS-Team Scopus Importer:2023-11-06

TuneIn: A Web-Based Interface for Practicing Choral Parts - Rosenzweig, Sebastian; Dietz, Lukas; Graulich, Johannes; Müller, Meinard (Demos and Late Breaking News of the International Society for Music Information Retrieval Conference (ISMIR), 2020)

Tuning Systems of Traditional Georgian Singing Determined from a New Corpus of Field Recordings - Scherbaum, Frank; Mzhavanadze, Nana; Rosenzweig, Sebastian; Müller, Meinard (Musicologist, 2022)
In this study we examine the tonal organization of the 2016 GVM dataset, a newly-created corpus of high-quality multimedia field recordings of traditional Georgian singing with a focus on Svaneti. For this purpose, we developed a new processing pipeline for the computational analysis of non-western polyphonic music which was subsequently applied to the complete 2016 GVM dataset. To evaluate under what conditions a single tuning system is representative of current Svan performance practice, we examined the stability of the obtained tuning systems from an ensemble-, a song-, and a corpus-related perspective. Furthermore, we compared the resulting Svan tuning systems with the tuning systems obtained for the Erkomaishvili dataset (Rosenzweig et al., 2020) in the study by Scherbaum et al. (2020). In comparison to a 12-TET (12-tone-equal-temperament) system, the Erkomaishvili and the Svan tuning systems are surprisingly similar. Both systems show a strong presence of pure fourths (500 cents) and fifths (700 cents), and 'neutral' thirds (peaking around 350 cents) as well as 'neutral' sixths. In addition, the sizes of the melodic and the harmonic seconds in both tuning systems differ systematically from each other, with the size of the harmonic second being systematically larger than the melodic one.
CRIS-Team WoS Importer:2023-03-03